2020
DOI: 10.1159/000507812
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Differences in the Uncanny Valley Effect

Abstract: Background: Due to declining birthrates and an increasing aging population, shortage of the caregiving labor force has become a global issue. Among various efforts toward the solution, introducing robotic products for assistance could provide an effective way to help older adults in their daily lives. As previous studies have indicated that older adults' acceptance of robots is lower than that of younger adults, enhancing older adults' acceptance of robots is imperative. Because older adults' first impressions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
(56 reference statements)
1
11
0
Order By: Relevance
“…The least preferred feature was the lower body as participants preferred to see the robot have legs to engage in leg exercises as well. These findings are consistent with previous studies comparing older age groups' preferences in robots against other groups [76][77][78]. It was consistently found that older adults preferred features that were more human-like as they were more familiar with human appearances.…”
Section: Robot Features and Alternative Activitiessupporting
confidence: 91%
“…The least preferred feature was the lower body as participants preferred to see the robot have legs to engage in leg exercises as well. These findings are consistent with previous studies comparing older age groups' preferences in robots against other groups [76][77][78]. It was consistently found that older adults preferred features that were more human-like as they were more familiar with human appearances.…”
Section: Robot Features and Alternative Activitiessupporting
confidence: 91%
“…Studies that focused on hardware design suggest that consumers prefer humanoid social robots over zoomorphic‐ and machine‐like robots (e.g., Belanche et al., 2020; Chu et al., 2019; Tu et al., 2020; Walters et al., 2008). A potential explanation for this preference might be that an embodied, humanoid robot increases consumers’ mind perceptions and positive personality attributions (e.g., Broadbent et al., 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is uncertain if the non-humanlike interfaces paired with a real human voice will be favored equally compared to a human-like interface paired with a robotic voice. Prior studies found that the uncanny valley effect positively impacts consumers' outcome behaviors, including the intention to use a robot (Tu et al, 2020) and the intention to engage with the bot (Moriuchi, 2021). Tu et al (2020) found that users preferred human-like robots over nonhumanlike robots, regardless of their robot function.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Prior studies found that the uncanny valley effect positively impacts consumers' outcome behaviors, including the intention to use a robot (Tu et al, 2020) and the intention to engage with the bot (Moriuchi, 2021). Tu et al (2020) found that users preferred human-like robots over nonhumanlike robots, regardless of their robot function. In a different context, Moriuchi (2022) found that anthropomorphism positively impacts patients' self-disclosure.…”
Section: Hypotheses Developmentmentioning
confidence: 99%